Budget Impact Analysis of Treatment Flow Optimization in Epilepsy Patients: Estimating Potential Impacts with Increased Referral Rate to Specialized Care - Masaki Iwasaki; Takashi Saito; Akiko Tsubota; Tatsunori Murata; Yuta Fukuoka; Kazutaka Jin (Journal of Health Economics and Outcomes Research)
**Objectives:** We developed a Markov model to simulate a treatment flow of epilepsy patients who refer to specialized care from non-specialized care, and to surgery from specialized care for estimation of patient distributions and expenditures caused by increasing the referral rate for specialized care.